Multiple myeloma: methods and protocols - Heuck, Christoph; Weinhold, Niels (Methods in molecular biology, 2018)
This volume provides a thorough guide of the study of multiple myeloma (MM)-from sample acquisition to the performance of molecular tests, and also discusses difficulties that arise during quality control and interpretation of results. The chapters in this book cover topics, such as next-generation-flow-based methods for detection of minimal residual disease and circulating tumor cells; Cytometry by Time-of-Flights (CyTOF); a droplet digital PCR approach for finding contamination in patients' samples; genome-wide investigation of the methylation and hydroxymethylation status of cytosines; and a microfluidic approach for creating nanoparticles. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Cutting-edge and comprehensive, Multiple Myeloma: Methods and Protocols is a valuable resource for molecular scientists and laboratory supervisors working with MM samples, and any investigator conducting studies in this field
Includes bibliographical references and index
Keywords: Plasmozytom